Bands, resonances, edge singularities and excitons in core level spectroscopy investigated within the dynamical mean-field theory - Haverkort, Maurits W.; Lu, Yi (epl, 2014)
Using a recently developed impurity solver we exemplify how dynamical mean-field theory captures band excitations, resonances, edge singularities and excitons in core level x-ray absorption spectroscopy (XAS) and core level photo electron spectroscopy (cPES) on metals, correlated metals and Mott insulators. Comparing XAS at different values of the core-valence interaction shows how the quasiparticle peak in the absence of core-valence interactions evolves into a resonance of similar shape, but different origin. Whereas XAS is rather insensitive to the metal insulator transition, cPES can be used, due to nonlocal screening, to measure the amount of local charge fluctuation.